2016
DOI: 10.1111/1471-0528.14257
|View full text |Cite
|
Sign up to set email alerts
|

Obstetric and neonatal complications in pregnancies conceived after oocyte donation: a systematic review and meta‐analysis

Abstract: Oocyte donation pregnancies have increased risk of a range of obstetric and neonatal complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
81
3
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 140 publications
(88 citation statements)
references
References 51 publications
3
81
3
1
Order By: Relevance
“…Five meta-analyses on pregnancy complications and perinatal outcomes after OD cycles are available in the literature [151155]. Unfortunately, these meta-analytic data were obtained without any adjustment for confounders and including studies with very high risk of biases.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Five meta-analyses on pregnancy complications and perinatal outcomes after OD cycles are available in the literature [151155]. Unfortunately, these meta-analytic data were obtained without any adjustment for confounders and including studies with very high risk of biases.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, the last systematic review with meta-analysis [155] included, after search for original studies reporting at least five OD pregnancies with a control group of pregnancies conceived by conventional IVF/ICSI or NC and case series with > 500 cases, 35 studies reporting one or more pregnancy and perinatal complications were analyzed. The risk of PIH (aOR 2.30, 95 % CI 1.60 to 3.32), PE (aOR 2.11, 95 % CI 1.42 to 3.15), LBW (aOR 1.53, 95 % CI 1.16 to 2.01), PTB (aOR 1.75, 95 % CI 1.39 to 2.20) and CS (aORs 2.20, 95 % CI 1.85 to 2.60) was higher in OD than in IVF singleton pregnancies, whereas in multiple pregnancies only the incidence of PIH (aOR 2.45, 95 % CI 1.53 to 3.93) and PE (aOR 3.31, 95 % CI 1.61 to 6.80) was increased [155].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In making this decision, the increased risks of pregnancy complications in connection with gestational surrogacy must be taken into account. A meta‐analysis showed that the risk of hypertension, preeclampsia and cesarean section was higher among women who had used oocyte donation, as in the case of gestational surrogacy, compared with IVF singleton pregnancies where the oocyte came from the women who carried the pregnancy .…”
Section: Discussionmentioning
confidence: 99%